The internal kinematic of star-forming regions in interacting galaxies - Firpo, V. (2019)
Star formation processes can be found in colliding galaxies, where the gas compression can trigger the formation of giant star-forming regions. We present the results from a detailed kinematic analysis in a sample of HII regions located in three strongly interacting galaxies. The velocity dispersion and the luminosity of the multiple-components analyzed in the emission-line profiles suggest that these star-forming objects correspond to giant complexes. In addition, the star formation rates and the ionization state in these regions revealed the presence of ongoing star formation events.